Inovasi dan Strategi Pengembangan Produk : Studi Pada UMKM Era Digital - Linda Lia Agustian; Zalfa Nada Amalia; Afifah Rizka Ramadhani; Sobakh Zidni Nabila; Ilma Trijayanti (Universitas Muhammadiyah Surakarta, 2026)
Usaha Mikro, Kecil dan Menengah (UMKM) has challenges and opportunities in the constantly changing digital world. In order to remain competitive, UMKM emphasizes innovation in product development and adapting to customer needs and preferences. Utilizing technology such as social media, e-commerce, and artificial intelligence (AI) speeds up the innovation process from ideation to product launch. Pendekatan based on data and focused on customers makes them the key to creating relevant products. In addition, training with digital technology and collaboration with daring platforms increase UMKM's innovative capacity. The success of digital transformation is based on innovative strategy integration and adaptability to changing market conditions. Because of this, collaboration between product innovation and technology use is crucial to creating a strong foundation for UMKM in Indonesia.